Isobar Configurations in the Ground State of Nuclei. Effective Polarization of an Isobar; Russian Physics Journal; Vol. 58, iss. 11 - Banin R. O.; Glavanakov I. V. Igor Vladimirovich; Tabachenko A. N. Aleksandr Nikitich (2016, 2016)
Title screen